Synthesis, Characterization and Anticancer Activity of Chitosan Schiff Base / PEG Blend Doped with Gold and Silver Nanoparticles in Treatment of Breast Cancer Cell Line MCF-7 - Maha Aldabbagh; Baker F. Abdallaha; Nibras Y. Abdulla; Ibraheem J. Ibraheem (College of Pharmacy University of Baghdad, 2024)
In the present study, chitosan Schiff base has been prepared from chitosan reaction with the para chloro benzaldehyde. The AuNPs and AgNPs were manufacture by extract of onion peels as a reducing agent. The AuNPs and AgNPs that have been synthesized were characterized through UV-vis spectroscopy the XRD analyses and SEM microscopy. The polymer blends of the chitosan / PEG has been prepared through using the approach of solution casting. Chitosan Schiff base / PEG Au and Ag nano-composites were synthesized nano composites and polymer blends have been characterized by FTIR which confirm the formation of Schiff base by revealing a new band of absorption at 1693 cm-1 as a result of the (C=N) imine group. FESEM, DSC and TGA confirms the thermal stability of the prepared polymer blends and nanocomposites, nano composites have shown good results in inhibiting breast cancer cell line MCF-7, IC50 of nanocomposite = 19.44 µg / mL.